Lower Lip and Chin Reconstruction with Functional Myocutaneous Gracilis Flap - Spaggiari, Antonio; Benanti, Elisa; Starnoni, Marta; Sala, Pietro; Baccarani, Alessio; Santis, Giorgio De (Indian Journal of Plastic Surgery, 2019)
Lower lip is an important anatomical unit in daily life activities, and its proper functional and aesthetic reconstruction is crucial. In the literature, both locoregional and microsurgical flaps have been described in lower lip reconstruction. Few authors have reported lower lip reconstruction with gracilis free flap. We describe a case of wide lower lip and chin avulsion caused by human bite reconstructed with an innervated gracilis free flap raised with its overlying skin paddle. The gracilis flap was harvested with a skin paddle of 7 × 5 cm, and vascular and nervous anastomoses were performed. At 9-month follow-up, an electromyography showed high muscle activities observed in the central part of the flap, and the patient achieved good oral functions reported with daily life activities. Raising the flap with the overlying skin paddle allowed us to avoid morbidity in other donor sites, avoid scar retraction of the skin graft on the gracilis that could limit its movement, and plan aesthetical refinements such as hair transplantation or tattoo of the beard on the skin.
Keywords: gracilis myocutaneous free flap; human bite; lip replantation; lower lip reconstruction